AUTHENTIC ASSESSMENTS ON STUDENTS’ SPEAKING MOTIVATION IN ENGLISH FOR TOURISM OF AMBARUKMO TOURISM INSTITUTE OF YOGYAKARTA - Palupiningsih, Angesti (Kepariwisataan: Jurnal Ilmiah, 2018)
This research aims at (1) revealing the differences of motivation between the students who are assessed using authentic assessment and those who are not in the English speaking practices and 2) trying out whether or not authentic assessment is more effective than non authentic assessment on the students’ motivation to deal with English speaking practices of Ambarrukmo Tourism Institute. This study was a quasi-experimental study using nonequivalent with one control group and one experimental group design. The data collecting instruments was a questionnaire for students’ motivation measurement. The validity of the instruments was gained using expert judgment and item validity. Bivariate Pearson was employed to check the item validity, whereas the reliability employed Alpha Cronbach. To see the difference in the effect of authentic assessment to the students’ motivation, the data were analyzed using the t-test at the significance level of 5%. The results are as follows. (1) There is a different effect of the authentic assessments on the students’ motivation. (2) Authentic assessment is more effective than non authentic assessment at improving the students’ motivation to deal with English speaking practices of Ambarrukmo Tourism Institute. Keywords: authentic assessments, students’ motivation, english speaking practices